Essential Role of Histone Replacement and Modifications in Male Fertility - Wang, Tong; Gao, Hui; Li, Wei; Liu, Chao (Frontiers in Genetics, 2019)
Spermiogenesis is a complex cellular differentiation process, that the germ cells undergo a distinct morphological change, and the protamines replace the the core histones to facilitate chromatin compaction in the sperm head. Recent studies show the essential roles of epigenetic events during the histone-to-protamine transition. Defects in either the replacement or the modification of histones might cause male infertility with azoospermia, oligospermia or teratozoospermia. Here, we summarize recent advances in our knowledge of how epigenetic regulators, such as histone variants, histone modification and their related chromatin remodelers, facilitate the histone-to-protamine transition during spermiogenesis. Understanding the molecular mechanism underlying the modification and replacement of histones during spermiogenesis will enable the identification of epigenetic biomarkers of male infertility, and shed light on potential therapies for these patients in the future.